Legal Protection of Children as Victims in Restorative Justice Based on Justice Value - Muhammad Ansori Lubis; Muhammad Yassid; Novi Juli Rosani Zulkarnain (UNISSULA, 2022)
The research purpose of this study is to determine the causes of children becoming victims of criminal acts and the legal protection of children as victims of justice-based crimes. approach method using normative juridical, research results which state that the protection of human rights for children who are victims of crimes is regulated in law as a legal protection for the State's obligations to the Indonesian people in ensuring the implementation of fundamental rights. The process of protecting and upholding human rights is carried out based on the state ideology, namely Pancasila which prioritizes human values, respecting the human rights of every citizen, both adults and children